VP15 A Comparison Of Reporting In United Kingdom Health Technology Assessment And Other Systematic Reviews. (2017) - Carroll, Christopher; Kaltenthaler, Eva
Abstract : INTRODUCTION: A recent study claimed that increasing numbers of reviews are being published and many are poorly conducted and reported (1). The aim of the present study was to assess how well reporting standards in systematic reviews published in 2014 in the United Kingdom Health Technology Assessment (UK HTA) monograph series compared with the reporting in Cochrane and other "non-Cochrane" systematic reviews from the same year, as reported by Page et al. (1). METHODS: All relevant UK HTA programme systematic reviews published in 2014 were identified. After piloting of the form, two reviewers each extracted relevant data on conduct and reporting from these reviews. These data were compared with data for Cochrane and "non-Cochrane" systematic reviews from 2014, as published by Page et al. (1). All data were tabulated and summarized. RESULTS: There were 30 UK HTA programme systematic reviews and 300 other systematic reviews, including Cochrane reviews (n = 45). Fewer UK HTA reviews covered therapeutic and pharmaceutical topics (53 percent and 20 percent respectively) than Cochrane (100 percent and 51 percent). The percentage of HTA reviews with required elements of conduct and reporting was frequently very similar to Cochrane and much higher than all other systematic reviews: for example, availability of protocols (90 percent, 98 percent and 16 percent respectively); the specification of study design criteria (100 percent, 100 percent, 79 percent); the reporting of outcomes (100 percent, 100 percent, 78 percent), quality assessment (100 percent, 100 percent, 70 percent) and other processes; the searching of trial registries for unpublished data (70 percent, 62 percent, 19 percent); reporting of reasons for excluding studies (91 percent, 91 percent and 70 percent) and reporting of authors' conflicts of interest (100 percent, 100 percent, 87 percent). However, HTA reviews compare less favourably with Cochrane and other reviews in the assessment of publication bias and reporting overall numbers of patients in the review. CONCLUSIONS: UK HTA systematic reviews are often produced within a specific policy-making context and cover a greater variety of topics than Cochrane reviews. This has implications for timelines, tools and resources. However, they still tend to present standards of conduct and reporting equivalent to "gold standard" Cochrane reviews and are superior to systematic reviews more generally.